The Relationship of Knowledge, Attitudes, and Actions of the Community with the Environmental Sanitation of the Region Fish Auction on the Coast of Kendari Bay (Study of Environmental Change Material Class X SMA) - Bulan, Wa Ode Sari; Amiruddin; Suama, I Wayan (Indonesian Journal of Agriculture and Environmental Analytics, 2023)
The phenomenon of environmental sanitation behavior among the public is very worrying, many factors influence the behavior of environmental sanitation such as knowledge, attitudes and actions. This study aims to determine the relationship between knowledge, attitudes, and actions of the community with environmental sanitation of the fish auction area on the coast of Kendari Bay. This type of research is a correlational study. The population of this study is the community in the Fish Auction Area which amounts to 171 heads of families (KK). The results of statistical tests show that knowledge is significantly related to environmental sanitation (p<0,05), Community attitudes are significantly related to environmental sanitation (p<0,05), But community actions do not relate significantly to environmental sanitation (p>0,05).